The Impact of Trade on Poverty in Sub-Saharan Africa: Do Sources Matter? - Sunge, Regret; Kumbula, Nyasha B; Makamba, Biatrice S (International Journal of Business, Economics and Management, 2021)
Global trade development has provided noteworthy global poverty gains since the 1990s. Accordingly, Africa has gradually engaged itself in trade and trade policy reforms through multilateral and regional trade agreements among other initiatives. Nonetheless, poverty levels in the Sub-Saharan Africa (SSA) region remain relatively high. Recognizing that existing evidence on trade-poverty nexus is based on aggregate trade, we provide a new perspective on SSA by disaggregating trade by sources for the period 2003-2017. We employed the Generalised Method of Moments (GMM) estimation of a panel data model derived from the Modified Basic Household Model and Neo-Conservative Poverty Theory for analysis. The results document poverty gains from trade liberalization, with the extent varying according to sources. Specifically, trade from MENA and within SSA was found to offer more gains. Furthermore, findings suggest that poverty gains from trade are strengthened with better institutional quality. It follows that to accelerate poverty gains from trade liberalization, SSA should promote intra-Africa trade as well as trade with MENA countries. To accelerate the gains, Africa has to invest in better institutions, in particular, to improve governance and corruption eradication.